2021
DOI: 10.1002/elps.202000236
|View full text |Cite
|
Sign up to set email alerts
|

Developments and applications of separation and microfluidics methods coupled to electrospray mass spectrometry in glycomics of nervous system gangliosides

Abstract: Gangliosides are particularly abundant in the nervous system (NS) where their pattern and structure in a certain milieu or a defined region exhibit a pronounced specificity. Since gangliosides are useful biomarkers for diagnosis of NS ailments, a clear‐cut mapping of individual components represents a prerequisite for designing ganglioside‐based diagnostic procedures, treatments, or vaccines. These bioclinical aspects and the high diversity of ganglioside species claim for development of specific analytical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 85 publications
(133 reference statements)
0
5
0
Order By: Relevance
“…Advances in high performance liquid chromatography (HPLC) and MS have greatly promoted metabolomics analysis. MS and HPLC can be combined for unknown endogenous or exogenous metabolites characterization in complicated biological samples [ [54] , [55] , [56] ]. However, the combination of these technologies requires expensive equipment, complicated sample preparation and long test time [ 57 ].…”
Section: Main Metabolic Molecules Detecting Methodsmentioning
confidence: 99%
“…Advances in high performance liquid chromatography (HPLC) and MS have greatly promoted metabolomics analysis. MS and HPLC can be combined for unknown endogenous or exogenous metabolites characterization in complicated biological samples [ [54] , [55] , [56] ]. However, the combination of these technologies requires expensive equipment, complicated sample preparation and long test time [ 57 ].…”
Section: Main Metabolic Molecules Detecting Methodsmentioning
confidence: 99%
“…Thus, the MS screening followed by CID MS/MS required only 500 fmols of material. For these reasons, over the past few years, this bioanalytical strategy demonstrated for the determination of glycosphingolipid markers of brain tumors could be developed into an efficient tool, largely applied to glycomics of human nervous system [ 214 ].…”
Section: Secondary Brain Tumorsmentioning
confidence: 99%
“…Several devices with different combinations of the applied electric field and separation technique are commercially available 21,22 . Numerous studies using IMS based on temporal-separation have been reported for the analysis of gangliosides, offering separation of isomeric ganglioside species and deep characterization of the ganglioside lipidome 16,17,[23][24][25][26][27][28][29][30][31][32][33][34] . In contrast, spatialseparation based IMS for gangliosides analysis has received limited attention 35 , despite its potential for increased sensitivity as shown in proteomics and lipidomics studies [36][37][38][39][40][41][42][43][44] .…”
Section: Introductionmentioning
confidence: 99%